Karakteristik bio-briket berbahan baku batu bara dan batang/ampas tebu terhadap kualitas dan laju pembakaran - Nurhalim Nurhalim; Rochim Bakti Cahyono; Muslikhin Hidayat (Jurnal Rekayasa Proses, 2018)
Indonesia has a very large fossil fuel source such as coal. In Indonesia, almost all power plants and industries use coal as solid fuel. Burning coal produces fly ash, bottom ash, poisonous gas and unused coal residue. The coal waste is commonly found in mining operations, abandoned mining areas, laboratories and power plants. This problem could be solved by producing bio-briquette using the coal waste. In this study, laboratory scale pyrolysis and non pyrolysis methods were used to produce bio-briquette using the coal waste with measurement of proximate analysis and burning rate. Pyrolysis was carried out at constant temperature of 400 oC for 2 hours. The total weight of briquette sample as much as 99.87 g was burnt at 400 oC with sufficient air space in the furnace. The waste coal was mixed with biomass bagasse and sugar cane stems before the briquetting process. The composition of the briquette material was 50 g of coal waste, 30 g of sugar cane biomass, and 10 g of bagasse. To form the briquette, tapioca was used as adhesive in addition to 5 g of clay with 50 mesh of size and application of 50 kg/cm2 pressure. The result of proximate analysis and combustion of the non-pyrolysis bio-briquette showed that non-pyrolysis bio-briquette contained 4.17 % of moisture content, 18.39% of fly ash, 25.56% of ash content, 5157.87 cal/g of calorific value. The mass of of pyrolysis bio-briquette (50 g) decreased to 30 g during 30 minutes, the compulsion reached maximum speed on 1.93 g/s and the smoke disappeared on the 24th minute The pyrolysis process on coal waste decreased the smoke and the addition of biomass increased the calorific value of bio-coal briquette.